Design and Performance Analysis of Toothless Slip Type Magnetic Rotary Oil Well Pipe Tong. Issue 1 (1st March 2022) - Zheng, Jie; Bi, Cheng; Lu, Heng; Li, Zhenzhen; Yang, Xu; Yang, Yushan; Lu, Yuan; Dou, Yihua; Zhang, Yarong
Abstract: Although the current hydraulic power pipe tong can improve efficiency and reduce strength, there are still some deficiencies. Among them, the inevitable defects are a low degree of automation, high labor intensity, complex mechanical mechanisms, and high maintenance costs. In order to improve its performance, the principle of permanent magnet motor is applied to the processing of shackle of oil pipe tong, and a new type of magnetic rotary oil pipe tong is proposed. The design eliminates the complex planetary gear train transmission mechanism and hydraulic circuit in the traditional tightening device, simplifies the mechanism of the tightening device, reduces the size of the device, saves the manufacturing cost, improves the automation degree of the power tong and reduces the labor intensity of the workers. The triangular chuck is suitable for clamping pipe strings with different diameters. In addition, due to the use of toothless slips, the damage of the tightening device to the sleeve is reduced, the sleeve is protected and the service life of the sleeve is prolonged. Therefore, this new type of magnetic rotary tubing tong has a good application prospect in the up and down operation.